European governance: the new fiscal rules and social spending - Catherine Mathieu; Henri Sterdyniak (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
The reform of the European fiscal rules came into force on 30 April 2024. The new rules, like the former ones, impose a depressive bias on domestic fiscal policies, leaving Member States' no fiscal room for manoeuvre. At the same time, the European Pillar of Social Rights sets ambitious targets for national social protection systems and requires an increase in social spending. A new form of governance would be required to prevent the fiscal rules from imposing restrictive fiscal policies to the expense of economic activity and, of more important, objectives (green transition, defence). This would require abandoning arbitrary targets for public deficits and debts and accepting, when needed, an increase in social contributions and taxation.
Keywords: E61; H53; I38; 330; Fiscal rules; European fiscal governance; European social model; Social spending